2009
DOI: 10.1351/pac-con-08-10-21
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of antimony from oxidizing ore deposits

Abstract: , at 25 °C in 0.100 mol dm -3 aqueous HNO 3 was also investigated. Equilibrium dissolved Sb concentrations were 3.3 ± 1.0 × 10 -7 and 7.7 ± 2.1 × 10 -8 mol dm -3 , respectively. These values have been used to re-evaluate the geochemical mobility of Sb in the supergene environment. It is concluded that the element is geochemically immobile in solution and in soils. This was in part validated by an orientation soil geochemical survey over the Bayley Park prospect near Armidale, New South Wales, Australia. Anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 29 publications
1
23
3
Order By: Relevance
“…Independent of the mechanisms behind the observed correlations, our findings are in contrast to previous studies concluding that Sb solubility was governed by Ca antimonate solubility in calcareous soils (Johnson et al, 2005;Oorts et al, 2008;Diemar et al, 2009;Okkenhaug et al, 2011), as this should have resulted in a negative correlation between Sb and Ca concentrations (Cornelis et al, 2011;Okkenhaug et al, 2012). Solubility calculations performed with log 10 K = À12.5 as equilibrium constant (Cornelis et al, 2011) confirmed that the soil water was indeed undersaturated with respect to Ca antimonate.…”
Section: Leaching Of Sb Under Drained Conditionscontrasting
confidence: 68%
“…Independent of the mechanisms behind the observed correlations, our findings are in contrast to previous studies concluding that Sb solubility was governed by Ca antimonate solubility in calcareous soils (Johnson et al, 2005;Oorts et al, 2008;Diemar et al, 2009;Okkenhaug et al, 2011), as this should have resulted in a negative correlation between Sb and Ca concentrations (Cornelis et al, 2011;Okkenhaug et al, 2012). Solubility calculations performed with log 10 K = À12.5 as equilibrium constant (Cornelis et al, 2011) confirmed that the soil water was indeed undersaturated with respect to Ca antimonate.…”
Section: Leaching Of Sb Under Drained Conditionscontrasting
confidence: 68%
“…This fact highlights the operational function of the sequential extraction. Previous studies of soils from abandoned mining areas have shown low levels of soluble Sb in soil (Baroni et al, 2000;Casado et al, 2007;Flynn et al, 2003;Gal et al, 2007;Hammel et al, 2000), indicating that Sb is geochemically immobile (Ainsworth et al, 1990a, b;Diemar et al, 2009;Flynn et al, 2003). The present results show that the mobility of Sb may be substantial higher in active mining areas like Xikuangshan, indicating a high level of bioavailable Sb in soil.…”
supporting
confidence: 56%
“…Diemar et al [32] [32] Nevertheless, it is possible that the above data may represent the approximate upper limits of the solubility of Sb V in the presence of Ca 2+ (aq) and Pb 2+ (aq) with short reaction times. With this in mind, it is noteworthy that Vitaliano and Mason [40] found that many of the natural specimens of stibiconite that they studied were X-ray-amorphous or poorly crystalline, and many contained appreciable amounts of calcium.…”
Section: Solubility Issuesmentioning
confidence: 90%
“…Some solubility data are available for roméite and bindheimite. [32] These minerals do not dissolve congruently in acid solution.…”
Section: Solubility Issuesmentioning
confidence: 99%
See 1 more Smart Citation